Morphological and Electrical Properties of Nanocellulose Compounds and Its Application on Capacitor Assembly. (30th April 2020) - Hernández-Flores, José Alfredo; Morales-Cepeda, Ana Beatriz; Castro-Guerrero, Carlos Fernando; Delgado-Arroyo, Filemón; Díaz-Guillén, Mario Roman; de la Cruz-Soto, Javier; Magallón-Cacho, Lorena; León-Silva, Ulises
Abstract : The rise for innovation in the electrical industry is strongly driven by development of new materials. Features of new materials are changing design paradigms for engineers. In this paper, the electrical properties of films of cellulose nanocrystals were measured. It was found that humidity affects the dielectric strength on the cellulose nanocrystals (CNCs). The dielectric strength was similar to the value of the industrial dielectric paper. The addition of plasticizer improved the flexibility of the material but lowered the dielectric strength. The films of CNC had an ordered arrangement, as suggested by the iridescence shown by them. The humidity content of the films was measured by thermogravimetric analysis. The CNC film was used for assembling a capacitor and compared to a capacitor assembled with dielectric paper.